ANALIS PENGARUH PERENCANAAN SUMBER DAYA MANUSIA TERHADAP KUALITAS FISIK BANGUNAN PADA DINAS PEKERJAAN UMUM KOTA BANDAR LAMPUNG - . Marbaki (e-JKPP, 2016)
Public Works Department City of Bandar Lampung is one of Bandar Lampung city government organization that is required to be able to provide excellent service in the sense of satisfaction of society and eliminate sekicil possible disappointments. To meet it should be supported by elements of adequate management and considering the breadth of the strategic plan should be formulated. Because the human resources at the Department of Public Works Bandar Lampung is quite interesting because factors analyzed human resources is an important factor in an organization then with the writer trying to raise the issue of human resources that exist in the Public Works Department in Bandar Lampung.Penelitiaan aims to analyze the influence of resource planning Public Works Department of the city of Bandar Lampung to improving the quality of school buildings in the Public Works Department of the city of Bandar Lampung, as well as to analyze the most dominant factor that has a significant effect on improving the quality of school buildings in the Public Works Department in Bandar Lampung.The method used in this research survey method and sampling through random sampling as many as 33 people in the category LS sample population, staff of Department of Public Works and the city of Bandar Lampung Bandar Lampung City Government Employees. The data collection techniques through field studies included interviews, observations and kuosioner and literature study.The relationship indicates that increasing or decreasing influence human resource planning Public Works Department of the City of Bandar Lampung will be followed by the increase or decrease in the physical quality of the Public Works Department building in the city of Bandar Lampung.